The Effects of Slip Conditions and Viscous Dissipation on the Stagnation Point Flow over a Stretching Sheet - Hasmawani, Hashim; Muhammad Khairul Anuar, Mohamed; Abid, Hussanan; Nazila, Ishak; Norhafizah, Md Sarif; Mohd Zuki, Salleh (2015)
The stagnation point flow of a vicous fluid towards a stretching sheet with slip conditions and viscous dissipation is studied. With the help of similarity transformation, the govering equations are converted to nonlinear ordinary differential equations and then solved numerically by Runge-Kutta-Fehlberg (RKF) technique. Numerical results for the local Nusselt number and skin friction coefficient as well as the temperature and velocity field are elucidated through tables and graphs. The influence of Prandtl number, stretching parameter, Eckert number, thermal and velocity slip parameter on the flow and heat transfer characteristics are analyzed and discussed.